2019
DOI: 10.1016/j.trsl.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The cellular basis of fibrotic tendon healing: challenges and opportunities

Abstract: Tendon injuries are common and can dramatically impair patient mobility and productivity, resulting in a significant socioeconomic burden and reduced quality of life. Because the tendon healing process results in the formation of a fibrotic scar, injured tendons never regain the mechanical strength of the uninjured tendon, leading to frequent re-injury. Many tendons are also prone to the development of peritendinous adhesions and excess scar formation, which further reduce tendon function and lead to chronic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
179
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(180 citation statements)
references
References 154 publications
(178 reference statements)
1
179
0
Order By: Relevance
“…Tendons are known to withstand substantial mechanical loads, yet various daily activities can cause chronic microdamage or acute injury to tendons . The healing response, especially of adult tendon, is insufficient to regenerate the tissue in situ as seen by scar formation at the site of injury that can result in chronic functional tendon deficiency . Understanding the contribution of tendon‐resident cells, their PCM, and the ECM that they construct during tendon development and homeostasis has important implications for tendon regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Tendons are known to withstand substantial mechanical loads, yet various daily activities can cause chronic microdamage or acute injury to tendons . The healing response, especially of adult tendon, is insufficient to regenerate the tissue in situ as seen by scar formation at the site of injury that can result in chronic functional tendon deficiency . Understanding the contribution of tendon‐resident cells, their PCM, and the ECM that they construct during tendon development and homeostasis has important implications for tendon regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Temporally controlled conditional deletions of these ECM components would address at which stage these proteins are required for tendon homeostasis and such studies already revealed distinct postnatal functions for biglycan and decorin . Lineage tracing experiments over the past several years made it abundantly clear that tendon tissue is host to more than one cell type . The questions that arise here are: (i) What components of the tendon ECM do individual cell types synthesize?…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations